Decision Support System to Determine The Price of Used Computer Based On Specification and Usage Duration Using Fuzzy Logic - Anik Vega Vitianingsih; Ravino Rahman; Anastasia Lidya Maukar; Seftin Fitri Ana Wati; Litafira Syahadiyanti (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
Using computers at work or others has many positive impacts, including a special program that simplifies data and media processing. Certain software applications will, for some time, require high computer specifications. Many people have computers and want to fulfill the application requirements by selling computers to upgrade the specifications. However, some people are not very knowledgeable about calculating the cost of a used computer. One of the things that are done to make it easier for users to determine the price of a used computer is to create a decision support system that will assist in determining the price of a used computer based on specifications and usage duration. The Fuzzy Logic method was used in this study by comparing the accuracy results of the Fuzzy Mamdani and Sugeno methods. The parameters are based on the purchase price of all computer components, including Processor, Motherboard, RAM, SSD, HDD, VGA, PSU, and Case and usage duration. Fuzzy Mamdani is proven to have a higher accuracy with a value of 71% when compared to Fuzzy Sugeno. Based on measurement findings and a comparison of the methods used. Therefore, Fuzzy Mamdani is recommended for future studies using the same parameters. The benefits of this research include a recommendation system that will make it simpler for the general public to determine the selling price of used computers based on their specifications and usage duration. Another advantage is that it makes it easier for the general population to become a reference when buying or selling used computers, mainly assembled computers.